Moral Education Strategies For Early Childhood In the Digital Age - Yusuf, M. Suyuti; Sulaiman, Baso (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to examine the impact of digital technology, especially gadgets, on the moral and moral development of early childhood in the digital era and formulate appropriate moral education strategies to overcome its negative impacts. This research uses qualitative research methods with a triangulation approach. Data is obtained through literature studies from various sources such as books, articles, and related journals. Data are obtained from literature relevant to the discussion. An in-depth analysis was conducted to understand the impact of digital technology on the moral and moral development of early childhood. The discussion results show that digital technology, especially gadgets, can hurt early childhood's moral and moral development. These negative impacts include technology addiction, decreased quality of social interaction, and lack of opportunities to learn moral and moral values. Therefore, the proper moral education strategy needs to be implemented. Recommended strategies include managing technology use time, setting a good example, supervising content children can access, getting used to interacting directly, teaching good moral and moral values, and involving children in social and humanitarian activities. By implementing these strategies, it is hoped that children can develop positive behaviors and reduce the negative impacts that may arise due to the use of digital technology.